Obesity and the paradox of mortality and heart failure hospitalization in heart failure with preserved ejection fraction - Mandviwala, Taher M; Basra, Sukhdeep S; Khalid, Umair; Pickett, June K; Przybylowicz, Ryle; Shah, Tina; Nambi, Vijay; Virani, Salim S; Deswal, Anita (International Journal of Obesity, 2020)
Limited data exist on the association of obesity with both hospitalization and mortality in patients with heart failure with preserved ejection fraction (HFpEF), especially in the real-world ambulatory setting. We hypothesized that increasing body-mass index (BMI) in ambulatory heart failure with preserved ejection fraction would have a protective effect on these patients leading to decreased mortality and hospitalizations. We studied the relationship between BMI and the time to all-cause mortality, time to heart failure (HF) hospitalization, and time to all-cause hospitalization over a 2-year follow-up in a national cohort of 2501 ambulatory HFpEF patients at 153 Veterans Affairs medical centers. Compared with normal BMI, overweight (HR 0.72; 95% CI 0.57-0.91), obesity class I (HR 0.59; 95% CI 0.45-0.77), obesity class II (HR 0.56; 95% CI 0.40-0.77), and obesity class III (HR 0.53; 95% CI 0.36-0.77) were associated with improved survival after adjustment for demographics and comorbidities. In contrast, the time to HF hospitalization showed an inverse relationship, with shorter time to HF hospitalization with increasing BMI compared with normal BMI; overweight (adjusted HR 1.30; 95% CI 0.88-1.90), obesity class I (HR 1.57; 95% CI 1.05-2.34), obesity class II (HR 1.79; 95% CI 1.15-2.78), and obesity class III (HR 1.96; 95% CI 1.23-3.12). However, time to first all-cause hospitalization was not significantly different by BMI groups. In a large, national ambulatory HFpEF cohort, despite the presence of the obesity paradox with respect to survival, increasing BMI was independently associated with an increased risk of HF hospitalization and similar risk of all-cause hospitalization. Future longer-term prospective trials evaluating the safety and efficacy of weight loss on morbidity and mortality, in patients with severe obesity and HFpEF are needed.